Cognitive-Philological Hybridization: Mapping Neural Story Grammars in the Manuscript Revisions of Modernist Epics - Djeukeu, Fouodji Edmonde Gloria (International Journal of Language and Literary Studies, 2026)
This article proposes and demonstrates a novel interdisciplinary methodology, cognitive-philological hybridization, to empirically analyse the compositional process of literary modernism. By integrating computational narrative analysis derived from cognitive neuroscience with traditional manuscript genetics, this study maps the evolution of narrative structure in two modernist epics: James Joyce's Ulysses and H.D.'s Helen in Egypt. Using digitized manuscript corpora from the James Joyce Digital Archive and the H.D. Papers at Yale, the research applies a story grammar parser—a computational model based on cognitive theories of narrative comprehension—to successive draft versions of key episodes. The parser quantifies structural features including event segmentation, character-goal hierarchies, and resolution coherence. Through longitudinal tracking of these metrics across revisions, the analysis reveals a previously unobservable cognitive patterning: both Joyce and H.D. systematically and measurably increased the cognitive processing demands of their narratives through strategic structural obfuscation, yet did so along divergent neuro-formal axes. Joyce’s revisions show a marked increase in embedded, interruptive event sequences that disrupt standard goal-directed parsing, while H.D.’s revisions intensify a layered, recursive goal hierarchy that demands sustained spatial-relations mapping. These findings challenge purely thematic or stylistic accounts of modernist difficulty, positing instead a quantifiable cognitive poetics of revision. This hybrid method establishes a new empirical foundation for genetic criticism, demonstrating that the modernist epic is not merely a textual artifact but a recorded trace of cognitive engineering, where the manuscript becomes a laboratory for restructuring the reader’s neural narrative architecture.